2020
DOI: 10.1017/s0007123419000590
|View full text |Cite
|
Sign up to set email alerts
|

The Trump Effect: An Experimental Investigation of the Emboldening Effect of Racially Inflammatory Elite Communication

Abstract: This article explores the effect of explicitly racial and inflammatory speech by political elites on mass citizens in a societal context where equality norms are widespread and generally heeded yet a subset of citizens nonetheless possesses deeply ingrained racial prejudices. The authors argue that such speech should have an ‘emboldening effect’ among the prejudiced, particularly where it is not clearly and strongly condemned by other elite political actors. To test this argument, the study focuses on the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 68 publications
1
63
0
Order By: Relevance
“…Extant research suggests that outgroup attitudes are extremely crystallized and stable, particularly in the short run (Tesler 2015;Henry and Sears 2009;Kinder and Sanders 1996). Recent work examining President Trump's 2016 presidential campaign finds that Trump didn't increase anti-immigrant attitudes in the US but rather activated attitudes that preceded his rise (Sides, Vavreck, and Tesler 2018) and emboldening racial conservatives to themselves voice and act on their pre-existing racial prejudice (Newman et al 2020). In fact, evidence from panel data suggests that a very gradual drop in prejudice toward African Americans and Latinos may be occurring during Trump's presidency, though it's difficult to understand the extent to which Trump himself is responsible for these changes.…”
Section: Endogeneitymentioning
confidence: 99%
“…Extant research suggests that outgroup attitudes are extremely crystallized and stable, particularly in the short run (Tesler 2015;Henry and Sears 2009;Kinder and Sanders 1996). Recent work examining President Trump's 2016 presidential campaign finds that Trump didn't increase anti-immigrant attitudes in the US but rather activated attitudes that preceded his rise (Sides, Vavreck, and Tesler 2018) and emboldening racial conservatives to themselves voice and act on their pre-existing racial prejudice (Newman et al 2020). In fact, evidence from panel data suggests that a very gradual drop in prejudice toward African Americans and Latinos may be occurring during Trump's presidency, though it's difficult to understand the extent to which Trump himself is responsible for these changes.…”
Section: Endogeneitymentioning
confidence: 99%
“…According to Pew Research, Asian Americans are also more likely than Latina/os and whites to note that they are the targets of discrimination (López, Ruiz and Patten, 2017). Some have found that discrimination, particularly inflammatory rhetoric communicated by leaders, influences various political behavior outcomes (McClain et al, 2009, Oskooii, 2018, Newman et al, 2019. Within this line of work, we further argue that there has been a resurfacing of xenophobic fears against Asian Americans during this pandemic.…”
Section: Asian Americans Partisanship and Exclusionmentioning
confidence: 61%
“…The pandemic and associated xenophobia could very well be a flashpoint for Asian Americans and contribute to a prolonged shift in party identification. We also see it valuable as a next step to conduct social experiments which prime "Chinese Virus"-related exclusion among Asian Americans to see how that affects partisan attitudes in similar manners that (Kuo, Malhotra and Mo, 2017) and (Newman et al, 2019)…”
Section: Discussionmentioning
confidence: 99%
“…We programed our survey using Qualtrics. After providing informed consent and answering demographic questions, respondents answered questions about identity, other questions used in larger surveys, such as the American National Election Study and the 2008 National Asian American Survey (Ramakrishnan et al 2012), and in previous candidate evaluation and political behavior research (Adida, Davenport and McClendon 2016; Lerman, McCabe and Sadin 2015; Newman et al n.d.), including questions that measure candidate gender stereotypes (Dolan 2014b) used in other research on women candidates (Merolla, Sellers, and Lemi 2017), and questions that reflect past theories of evaluations of Black women candidates (Philpot and Walton Jr. 2007, 60) that use the notion of “linked fate” (Dawson 1994). Participants were randomly assigned to one of six experimental conditions using the Qualtrics randomizer 7…”
Section: Methodsmentioning
confidence: 99%